2018
DOI: 10.1007/s11365-018-0496-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exploitation and exploration on the innovative as outcomes in entrepreneurial firms

Abstract: The main aim of this study is to establish the effect of the Exploitation and Exploration; and the influence of these learning flows on the Innovative Outcome (IO). The Innovative Outcome refers to new products, services, processes (or improvements) that the organization has obtained as a result of an innovative process. For this purpose, a relationship model is defined, which is empirically contrasted, and can explains and predicts the cyclical dynamization of learning flows on innovative outcome in knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…Eco-innovation is a key element because it increases value for both producers and consumers while reducing negative impacts on the environment [73]. In a global context, where change is increasing and innovation is disruptive [74], sources of competitive advantage must be created [75], and differentiation strategies must be developed through eco-innovation. Investment in eco-innovation enables firms not only to gain a privileged market position but also to maintain this position in the long term.…”
Section: Eco-innovationmentioning
confidence: 99%
“…Eco-innovation is a key element because it increases value for both producers and consumers while reducing negative impacts on the environment [73]. In a global context, where change is increasing and innovation is disruptive [74], sources of competitive advantage must be created [75], and differentiation strategies must be developed through eco-innovation. Investment in eco-innovation enables firms not only to gain a privileged market position but also to maintain this position in the long term.…”
Section: Eco-innovationmentioning
confidence: 99%
“…The value of innovative processes focusing on exploration and exploitation processes to obtain an innovative outcome (IO) has been studied. IO has been defined as new products, services or processes (or improvements) that the organisation has obtained as a result of an innovative process (Crossan and Apaydin, 2010; Vargas et al , 2018). Some empirical studies have shown that firms that explore generate new and more innovative technologies in the long term but infrequently (Greve, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, other works propose theoretical models that are original but which, in the end, are not empirically contrasted in quantitative or qualitative studies. Thus, this area remains a topic of interest in research (Katila and Chen, 2008; Crossan and Apaydin, 2010; Teece, 2012; Vargas et al , 2018; Wilden et al , 2018). In this paper, then, we empirically test our new model in a quantitative study with significant conclusions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies illustrated that innovation and innovative capability (IC) are also related to SEP [35]. The linkage of inner capacity with abilities that comes with something new is known as IC-IC is directly correlated with the nature of SEP [35]. The IC of an individual comes in the form of entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%